Citizenship of Algerians During the French Colonial Period Between 1865 to 1919 - Badra Gündoğdu (Skad)
This study seeks to shed light on the issue of Algerian citizenship during the French colonial period between 1865 and 1919. And on the practices of the French administration in the context of its colonial policy of granting Algerians the status of French citizens and naturalizing them with French nationality under a series of unjust laws starting with the Senatus Consult Act of 1865 and the Crémieux Decree of 1870, passing through the People's Law of 1871, and ending with the Law of 4 February 1919 and the so-called reforms it introduced. Where all these laws were considered unfair to the Algerians (the indigenous population) were at the service of the colonial administration and brought no good to the Algerian people, the owners of the land, who rejected the policies of colonialism, colonization, oppression, and resistance for a free and independent Algeria.This study aims to show that the French colonial administration made promises to Algerians by granting them French citizenship and granting them civil and political rights, but these promises were always conditional on a set of conditions accompanying Muslim Algerians leaving their Islam. This is an attempt by France to assimilate Algerians completely into the French entity and to eliminate everything that is Algerian, Islamic and Arab.